La paz social - Terrén, Ferro (Sapientia, 2014)
The value of peace in its social dimension, which finds its basis on rational and moral order of the society and has its roots in God himself, is meant to be highlighted. Aquinas speaks of peace in various places in its work and mainly in the four articles of the II-IIq. 29. Peace is the calmness that results from the order among the different parts of a whole. Peace is considered in itself (inner or personal peace) and in relation to other people (external or social peace). A human peace that finds its source in the background of hearts, and extends from there to the various groups in political or social peace.